Optical emission spectroscopy study on flashover along insulator surface due to particle contamination. (4th November 2014) - Tewari, Somesh Vinayak; Kshirsagar, R.J.; Roy, Amitava; Sarathi, R.; Sharma, Archana; Mittal, K.C.
Abstract The surface flashover behavior in ambient air and nitrogen are studied at a pressure of 1 kg/cm2 using optical emission spectroscopy. A high dc voltage is applied to Rogowski profile electrodes with polyoxymethylene as the insulator between the electrodes. Three different conditions of needle protrusion along the surface of polyoxymethylene are used to study the variation in spectral characteristics due to particle contamination. When the insulator is placed between the spark gap electrodes, the OES spectra are dominated by the Hα line in air and nitrogen medium. It was found that the intensity of N2+ (B-X) emission is less in air surrounding the insulator medium. The plasma temperature during bulk breakdown in air is 0.433 eV, which increases to 0.434 eV with the pressurized nitrogen, which further increases in the presence of insulator to 0.441 eV and 0.44 eV in nitrogen and air, respectively. The electron density is obtained from the N emission line at 746.8 nm and the estimated peak value is 2.85 × 1012 cm−3 in the presence of insulator. The plasma temperature decreases with increase in distance of particle contamination from cathode. The increase in electron density in air, as compared to nitrogen implies more material desorption in air which is also supported by the comparisons of Hα lines.